PERAN BRAND IMAGE MEMEDIASI PENGARUH GREEN MARKETING TERHADAP PURCHASE DECISION PRODUK KAI DROBE DI INSTAGRAM - Bachtiar, Bagas Dwi Arissaputra; Santika, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p14, 2023)
Fast fashion is a business philosophy in the fashion industry, namely mass production of clothing to meet market demands quickly. With large-scale fashion production has led to the accumulation of clothing waste and textile waste pollution to the environment. Kai drobe is one of the thriftshop businesses that focuses on selling on social media, especially Instagram, Kai drobe sells used clothes with one goal of reducing textile waste. This study aims to examine and explain the role of Brand Image in Mediating Green Marketing and Purchase Decisions. This research was conducted on Kai Drobe's Instagram account with a total sample of 100 respondents. The sample was determined using a non-probability sampling model, with a purposive sampling technique. The data analysis technique used is path analysis and Sobel test with SPSS program. The results showed that all hypotheses were accepted. Green Marketing has a positive and significant effect on purchase decisions, green marketing has a positive effect on brand image, brand image has a positive and significant effect on purchase decisions, brand image is able to mediate significantly on green marketing and brand image is able to significantly mediate purchase decisions